Método para linealizar la salida de un sensor - Quintero Camacho, Rigoberto (Ingeniería, 2008)
In this paper a simple method for lining a sensor is presented. The method consists in finding a fixed value for a resistance put parallel together with the variable resistance, an example, in which a termistor is lined, is shown as well, in order to test the method. This method is used for designing a voltage measuring circuit, where the output is required to be lineal.